Performance Analysis of Multi-Relay Assisted IoT Networks in Mixed Fading Environments: Multi-Relay Assisted IoT Networks in Mixed Fading Environments - Huang, Jiajia; Wei, Fusheng; Zhao, Jingming; Que, Huakun (EAI Endorsed Transactions on Scalable Information Systems, 2023)
This study delves into the realm of multi-relay assisted Internet of Things (IoT) networks within the context of mixed fading environments. Here, data transmission from the source to the destination is facilitated through a configuration involving multiple decode-and-forward relays. Specifically, our investigation revolves around mixed fading environments characterized by the first-hop relaying links conforming to a uniform distribution, while the second-hop relaying links exhibit Rayleigh fading. To bolster the overall efficacy of the network, we introduce two distinct relay selection criteria. The first criterion entails an optimal selection process hinging on the identification of the most proficient relay. This determination relies upon the evaluation of dual-hop relaying links. In contrast, the second criterion adopts a sub-optimal selection approach by singling out the optimal relay solely based on characteristics associated with the second-hop relaying links. The performance evaluation of the two aforementioned relay selection criteria entails the derivation of analytical expressions governing the system's outage probability. To validate the theoretical underpinnings presented in this research, we supplement our analysis with simulation results. Notably, our findings underscore the efficacy of augmenting network performance by augmenting the number of relays within the network topology.
Keywords: Multi-relay; IoT; outage probability; mixed fading